Effect of Fe3+ on the nutrient removal performance and microbial community in a biofilm system - Wu, Tong; Zhong, Le; Pang, Ji-Wei; Ren, Nan-Qi; Ding, Jie; Yang, Shan-Shan (Frontiers in Microbiology, 2023)
To meet stringent effluent discharge standards, Fe3+ is often used as a coagulant to improve chemical phosphorus(P) removal. While the use of Fe3+ ensures effective chemical P removal, it also has an impact on nitrogen(N) removal and microbial composition of biochemical treatment units. In this research, the influence of Fe3+ on N removal, microbial assembly, and species interactions was determined in a biofilm system. Results illustrated that maximum COD, NH4+-N, TN, and P removal efficiencies were achieved using 10 mg/L Fe3+, reaching 100%, 78.85%, 100%, and 95.8%, respectively, while Fe3+ concentrations of 15 and 30 mg/L, resulted in NH4+-N, TN, and COD removal being suppressed. The P removal efficiency of the system consistently remained at 100% despite the different concentrations of Fe3+. Norank_f_ PHOS-HE36 showed better resistance to high Fe3+ concentrations while the abundances of Tetrasphaera and Dechloromonas were inhibited. Determinism (50%) and stochasticity (50%) were found to equally contribute to microbial community assembly. Co-occurrence network analysis illustrated that with the presence of Fe3+, 60.94% of OTUs in the biofilm system exhibited positive interactions, while 39.06% were negative interactions. The stability of the system was dominantly affected by microbial cooperation and complemented by competition for resources or niche incompatibility. This study offers a broad insight into the influence of Fe3+ on biofilm systems and the response mechanisms, which are crucial to the effective utilization of inorganic salts in wastewater treatment systems.